The relationship between vicarious experience and mathematics achievement: Mediating effects of mastery experience and physical state - Khalid S. Al Umairi (Journal of Pedagogical Research)
The aim of this study is twofold: one is to examine the relationship between mathematics achievement and three sources of mathematics self-efficacy (social persuasion, vicarious experience, and physical state) separately through mastery experience as a mediator, and the other is to investigate the relationship between vicarious experience and mathematics achievement through physical state and social persuasion as mediators. The sample of this study comprised of 374 eighth-grade students from the Sultanate of Oman. A partial least square structural equation modeling by Smart PLS is employed to evaluate the data. The findings of this study indicate that sources of mathematics self-efficacy can predict mathematics achievement except vicarious experience. Mastery experiences and physical state fully mediate the relationship between vicarious experience and mathematics achievement. However, mastery experiences partially mediate the relationship between SP and mathematics achievement.